Effect Of Short-Term Community Based Intervention to Reduce the Prevalence of Under Nutrition in Under-Five Children - Jamra, Vishal; Bankwar, Vishal (National Journal of Community Medicine, 2013)
Background & Objectives: Malnutrition is a scourge for mankind especially among the developing world countries like India. The present study endeavors to find the factors responsible for this magnitude of under nutrition in under-5 in an urban slum area and also to find the effect of short term educational intervention and deworming on the status of under nutrition. Materials and Methods: This cross sectional intervention study was undertaken in slum area for a period of 6 months. In the first phase prevalence of under nutrition in under-5(age 6 months-5 years) was determined by carrying out door to door survey in the locality. This also included finding out the factors responsible for under nutrition. The weight for age criteria with IAP classification was used for the purpose. In the second phase intervention was done in children in form of health education of the parents and deworming of the children and again survey for under nutrition was done and the changes noted. Results: Out of the 281 children examined 22.1% were found to be malnourished with varying degrees of malnutrition. Various factors like age of the child, sex, socioeconomic status, literacy status of parents, birth order, parity, age at weaning, immunization status are associated with nutrition. After intervention improvement in weight was seen in 41 children. Conclusion: Proper health and nutritional education along with deworming may go a long way in decreasing the menace of under nutrition.